Mast Cells Exert Anti-Inflammatory Effects in an IL10−/− Model of Spontaneous Colitis - E. M. Lennon; L. B. Borst; L. L. Edwards; A. J. Moeser (Mediators of Inflammation)
Mast cells are well established as divergent modulators of inflammation and immunosuppression, but their role in inflammatory bowel disease (IBD) remains to be fully defined. While previous studies have demonstrated a proinflammatory role for mast cells in acute models of chemical colitis, more recent investigations have shown that mast cell deficiency can exacerbate inflammation in spontaneous colitis models, thus suggesting a potential anti-inflammatory role of mast cells in IBD. Here, we tested the hypothesis that in chronic, spontaneous colitis, mast cells are protective. We compared colitis and intestinal barrier function in IL10−/− mice to mast cell deficient/IL10−/− (double knockout (DKO): KitWsh/Wsh × IL10−/−) mice. Compared with IL10−/− mice, DKO mice exhibited more severe colitis as assessed by increased colitis scores, mucosal hypertrophy, intestinal permeability, and colonic cytokine production. PCR array analyses demonstrated enhanced expression of numerous cytokine and chemokine genes and downregulation of anti-inflammatory genes (e.g., Tgfb2, Bmp2, Bmp4, Bmp6, and Bmp7) in the colonic mucosa of DKO mice. Systemic reconstitution of DKO mice with bone marrow-derived mast cells resulted in significant amelioration of IL10−/−-mediated colitis and intestinal barrier injury. Together, the results presented here demonstrate that mast cells exert anti-inflammatory properties in an established model of chronic, spontaneous IBD. Given the previously established proinflammatory role of mast cells in acute chemical colitis models, the present findings provide new insight into the divergent roles of mast cells in modulating inflammation during different stages of colitis. Further investigation of the mechanism of the anti-inflammatory role of the mast cells may elucidate novel therapies.